REORIENTASI PENDIDIKAN ISLAM (Menimbang Tarbiyah Syari’ah Sebagai Alternatif) - Amrizal Amrizal (An-Nida', 2012)
Tarbiyah Syar’iyah is oriented education in accordance with the objective syar’i (maqasid syari’ah). Referring to the theory of maqashid syari’ah, the Islamic education should be oriented to: 1) The development of religion and religious sciences/religius (hifz al-din) and, 2) concept of humanitarian/humanis (hifz al-nafs), 3) rational and development of human intelligence (hifz al-‘aql), 4) maintenance of the interests of families, communities and national or social perpective (hifz al-nasl and hifz al-ummah), 5)insightful economic and welfare development (hifz al-mal), 6) insightful achievements in improving self-esteem people ( hifz al-‘aradh), 7) concept pragmatic (jalb al-mashalih), and 8) solutif-anticipatory (dar al-mafasid)